Family History of Breast Cancer and Breast Cancer Risk between Malays Ethnicity in Malaysia and Indonesia: A Meta-Analysis - Ricvan Dana NINDREA; Teguh ARYANDONO; Lutfan LAZUARDI; Iwan DWIPRAHASTO (Tehran University of Medical Sciences, 2019)
Background: Breast cancer is the most common cancer type in women not only in world but also in Malays ethnicity between Malaysia and Indonesia. Breast cancer has varying incidence in every country, but genetic factor by family history influence the incidence of breast cancer. This systematic review and meta-analysis was performed to determine family history of breast cancer and breast cancer risk between Malays ethnicity in Malaysia and Indonesia. Methods: This meta-analysis was conducted on published research articles on family history of breast cancer and breast cancer risk between Malays ethnicity in Malaysia and Indonesia published between Jan 1999 and Jul 2018 in the online article databases of PubMed, ProQuest and EBSCO. Pooled odds ratios (OR) were calculated with fixed and random-effect models. Publication bias was visually evaluated by using funnel plots and statistically assessed through Egger's and Begg's tests. Data were processed using Review Manager 5.3 (RevMan 5.3) and Stata version 14.2 (Stata Corporation). Results: We reviewed 1123 articles. There are 10 studies with number of samples 4511 conducted a systematic review and continued with Meta-analysis of relevant data. The results showed significant association between family history of breast cancer with breast cancer risk in Malays ethnicity in Malaysia and Indonesia (OR = 3.34 [95% CI 2.68-4.15, P<0.00001]). There was not significant publication bias for studies included in family history of breast cancer and breast cancer risk in Malays ethnicity in Malaysia and Indonesia Conclusion: This analysis confirmed the association of family history of breast cancer and breast cancer risk between Malays ethnicity in Malaysia and Indonesia.